2010
DOI: 10.1007/s12149-010-0429-z
|View full text |Cite
|
Sign up to set email alerts
|

Is contrast material needed after treatment of malignant lymphoma in positron emission tomography/computed tomography?

Abstract: PET/ceCT yielded more accurate findings than PET/ldCT in a limited number of cases. PET/ldCT may, therefore, be sufficient for routine PET/CT scanning for post-therapeutic assessment or restaging of lymphoma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Interestingly, a recent publication by Nakamoto et al suggests that PET/CT without contrast-enhanced CT is sufficient for lymphoma surveillance and therefore the use of PET/CT instead of CT surveillance could in fact reduce the overall exposure to ionizing radiation in HL survivors. 28 Attention to the health care costs of PET/CT surveillance is commanded in a period in which massive budget problems in public health care systems are obvious across most of Europe. The price per relapse diagnosed by routine PET/CT was US$ 50,778, which was slightly more than the US$ 38,736 -48,757 reported by Lee et al 20 The total costs of PET/CT surveillance are probably even higher because of the numerous supplementary investigations performed due to false positive PET/CT results.…”
Section: Routine Pet/ct Clinically Indicated Pet/ctmentioning
confidence: 99%
“…Interestingly, a recent publication by Nakamoto et al suggests that PET/CT without contrast-enhanced CT is sufficient for lymphoma surveillance and therefore the use of PET/CT instead of CT surveillance could in fact reduce the overall exposure to ionizing radiation in HL survivors. 28 Attention to the health care costs of PET/CT surveillance is commanded in a period in which massive budget problems in public health care systems are obvious across most of Europe. The price per relapse diagnosed by routine PET/CT was US$ 50,778, which was slightly more than the US$ 38,736 -48,757 reported by Lee et al 20 The total costs of PET/CT surveillance are probably even higher because of the numerous supplementary investigations performed due to false positive PET/CT results.…”
Section: Routine Pet/ct Clinically Indicated Pet/ctmentioning
confidence: 99%
“…We favoured this approach, which is similar to that used by other authors [20,24], because we felt that it was clinically more relevant, particularly with regard to treatment planning. In patients with liver metastases, for instance, knowledge of the affected liver segments, which we used as separate regions in our study, is more relevant for deciding between segmental resection, lobectomy or hemi-hepatectomy, than knowledge of the total number of lesions within the liver, or within each segment.…”
Section: Discussionmentioning
confidence: 98%
“…At present, there is no international consensus as to whether PET/CT, in general, should be performed with contrastenhanced CT, or whether unenhanced full-dose diagnostic or low-dose protocols are sufficient for the morphological confirmation of focal areas of increased tracer accumulation or their assignment to anatomical structures. For a mixed patient population with different types of malignant lymphoma, Nakamoto et al were able to show that intravenous contrast enhancement increases the accuracy of posttherapeutic (18)F-FDG PET/CT only in a limited number of cases (patient-based sensitivity, +4%; specificity, + 1%), and thus concluded that unenhanced low-dose PET/CT may be sufficient for routine diagnostic imaging in such patients [20]. Similar results were reported by Pfluger et al in a lesionbased analysis of patients with malignant melanoma, where the differences in sensitivity between unenhanced and contrast-enhanced (18)F-FDG PET/CT were only 3% in favour of the contrast-enhanced image -no difference was observed in terms of specificity [21].…”
Section: Discussionmentioning
confidence: 99%
“…Could a low-dose PET/CT be enough for disease staging, consequently decreasing radiation dose to the patient? Different groups have already studied this topic, 11–14 comparing sensitivity and specificity of a low-dose, noncontrast-enhanced PET/CT with a high-dose ceCT (coregistered with the PET acquisition or independently performed). These studies did not find any significant difference among two CT modalities regarding nodal or extranodal, even a low-dose PET/CT could detect more lesions.…”
Section: Discussionmentioning
confidence: 99%